Search for excited quarks in the γ plus jet final state in proton-proton collisions at √s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruhwirth, R.; Ghete, V. M.; Hartl, C.; et al. (ELSEVIER, 2014)
A search for excited quarks decaying into the gamma + jet final state is presented. The analysis is based on data corresponding to an integrated luminosity of 19.7 fb(-1) collected by the CMS experiment in proton-proton collisions at root s = 8 TeV at the LHC. Events with photons and jets with high transverse momenta are selected and the gamma + jet invariant mass distribution is studied to search for a resonance peak. The 95% confidence level upper limits on the product of cross section and branching fraction are evaluated as a function of the excited quark mass. Limits on excited quarks are presented as a function of their mass and coupling strength; masses below 3.5 TeV are excluded at 95% confidence level for unit couplings to their standard model partners. (C) 2014 The Authors. Published by Elsevier B.V.
Keywords: CMS; Physics; Photon; Jet; PARTON DISTRIBUTIONS; Astronomy & Astrophysics